2x squared - 3x
x(3x - 2)
Oh, dude, that's like basic math, right? So, 2x squared plus x squared is just 3x squared. It's like adding apples to apples, but with math. Easy peasy lemon squeezy!
3x squared - x squared = 2x squared
x^2+2x^2=3x^2
6x3 + 9x2 - 2x2 - 3x Before any grouping, take out the common factor, x, to give x*(6x2 + 9x - 2x - 3) = x*[3x*(2x + 3) - 1*(2x + 3)] = x*(2x + 3)*(3x - 1)
3x2-2x-8 = (3x+4)(x-2) when factored
(x + 1)(2x - 5)
(x - 1)(3x + 5)
6x^2, six x squared.
(x - 2)(2x + 7)
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.